Discourse, Identity and International Development Cooperation: China, Africa and FOCAC - Delgado, Daniel Lemus (Animo Repository, 2015)
This article analyses the relationship between discourse and identity in the case of the People’s Republic of China in Africa. It assumes that the interests of the Chinese government in Africa can be understood from a theoretical constructivist approach. So, the activities of International Development Cooperation of China into Africa are a result of material and ideational aspirations. Thus, the ties of China in Africa have been boosted by the identity of the Chinese state in the international arena. To understand how identity and interest are linked, this article analyses the official discourse of China in Forum on China Africa Cooperation. Thus,14 official discourses areanalyzed to determine how these discoursesreinforce theidentity of the Chinese state and how that identity is reflected in these discourses, inan intersubjectiveprocess.This article concludes that words and ideas have become an institutional mechanism that is consistent and well defined, and in which the relationship between China and Africa has been oriented.